Strategies for ALM: The Path to the Factory of the Future - Vukosavljević, Radomir; Mijanović, Marina (Journal of Production Engineering, 1994)
Permanent market changes require companies to adopt agile and flexible responses, especially a reduction in product development and lead times. This necessitates strategies for coordinating company resources. Advances in information processing enable the use of new 'smart' tools for modeling processes and resource allocation. The employee is at the center of this approach, enabling flexible responses and optimal utilization of all company resources. Environmental impacts must be considered in work organization and system layout optimization. This presentation discusses strategies for cost reduction, quality improvement, and increased efficiency.